2017
DOI: 10.1007/s40843-017-9128-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-controlled synthesis of Cu-based for the Rochow reaction

Abstract: The properties of materials are strongly dependent on their structures. The diffusion effect is a main kinetic factor that can be used to regulate the growth and structure of materials. In this work, we developed a systematic and feasible strategy to synthesize Cu 2 O solid spheres and hexahedrons by controlling the diffusion coefficients. These Cu 2 O products can be successively transformed into corresponding Cu hollow spheres and hexahedrons as well as CuO porous spheres and hexahedrons by controlling hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…; (3) focusing on different perspectives. For instance, some researchers paid their primary attention to the thermodynamics, while some others to kinetics, and the rest emphasized more on the electronic structures or effects of catalyst‐promoter systems themselves . In general, the synergetic interactions of promoters with the main active components of the catalysts in different systems are of interest but not very clear.…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
See 1 more Smart Citation
“…; (3) focusing on different perspectives. For instance, some researchers paid their primary attention to the thermodynamics, while some others to kinetics, and the rest emphasized more on the electronic structures or effects of catalyst‐promoter systems themselves . In general, the synergetic interactions of promoters with the main active components of the catalysts in different systems are of interest but not very clear.…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
“…The discovery of the indium promoter helped to explain the effects of Zn, Sn, and P. Zhang et al reported that in a Rochow‐Müller system, the catalytic function can be generated via two types of interfaces (Figure a) . “Interface” 1 is the “P−N junctions” generated between P‐type CuO and N‐type In 2 O 3 .…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
“…Powder X-ray diffraction (XRD) pattern demonstrates that the Cu 2 O nanocube has the characteristic peaks located at ∼30°, ∼36°, ∼43°, ∼62°, and ∼74°, ascribed to the (101), (111), (200), (220), and (311) facets, respectively (Figure S3). , The surface exposed Cu atom of Cu 2 O nanocube can provide anchor sites for PyTTA, which is important for conducting the following Schiff base reaction between PyTTA and TPA. , SEM image of as-made Cu 2 O/PyTTA-TPA COFs hybrid shows the uniform nanocube morphology (Figure S4). TEM image of Cu 2 O/PyTTA-TPA COFs nanocubes reveal that they have the typical core/shell structure (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The broad product distribution and the small impurities in the metallurgical grade silicon (i.e., Fe, Al, Ca, etc.) add to the complexity. ,,, Several Cu-based compounds such as CuO, Cu 2 O, CuCl, and also combinations thereof have been used as the catalyst precursors in the MCS synthesis. CuCl is regarded as efficient in this respect, since it not only reduces the induction period but also increases the selectivity toward M2 . Several other metals are reported to enhance the catalytic activity, selectivity, and stability of copper in the direct process. For example, there is a general agreement in the literature that zinc (Zn) increases the selectivity toward M2, , and that its copromotion with tin (Sn) results in a synergistic relationship that increases both reaction rate and M2 selectivity. , …”
Section: Introductionmentioning
confidence: 99%
“…The reaction between chloromethane (CH 3 Cl, also called methyl chloride) and silicon (Si) to synthesize methylchlorosilanes (MCS), also known as the Müller-Rochow Synthesis or the Direct Process, is currently the most convenient and economical way to produce MCS industrially. Almost 90% of the starting materials for current silicone manufacturing are obtained with MCS monomers. On an industrial scale, ground metallurgical grade silicon is mixed with a copper-based catalyst and minor amounts of various other promoter elements in a fluidized bed reactor under gaseous CH 3 Cl, at temperature and pressure ranging between 280–350 °C and 1–10 bar. , This quite unique gas (CH 3 Cl)–solid (Si)–solid (Cu-based catalyst) heterogeneous reaction exhibits a complicated dependency on reaction temperature, (partial) pressure(s), reactor type, residence time distribution, and phase/component interactions. , The latter incorporates nature, purity, size distribution, morphology, and proportion of silicon to copper catalyst precursor and promoters . Moreover, a range of methylchlorosilanes, (CH 3 ) x SiCl 4– x , is formed although the dominant and main product of interest is dimethyldichlorosilane, (CH 3 ) 2 SiCl 2 , also referred to as “M2” .…”
Section: Introductionmentioning
confidence: 99%